Creatine improves total sleep duration following resistance training days versus non-resistance training days among naturally menstruating females - Cruz, A. J. A. B.; Brooks, S. J.; Kleinkopf, K.; Brush, C. J.; Irwin, G. L.; Schwartz, M. G.; Candow, D. G.; Brown, A. F. (Nutrients, 2024)
Females historically experience sleep disturbances and overall poor sleep compared to males. Creatine has been proposed to impact sleep; however, the effects are not well known. The purpose of this study was to examine the effects of creatine supplementation on sleep among naturally menstruating females. Twenty-one participants completed a double-blind, randomized controlled trial in which they consumed 5 g creatine + 5 g maltodextrin or placebo, 10 g maltodextrin, daily for 6 weeks. Participants completed resistance training 2x/week using the TONAL® (Tonal Systems Inc., San Francisco, CA, USA) at-home gym. Pre- and post-testing assessed body composition, Pittsburgh Sleep Quality Index (PSQI), dietary intake, and muscular strength. Sleep was assessed nightly using an OURA® (Oulu, Finland) ring. Compared to the placebo group, those consuming creatine experienced significant increases in total sleep on training days (p = 0.013). No significant changes in chronic sleep and PSQI (pre-post) were observed. There was a significant increase in TONAL® strength score over time (p < 0.001), with no between-group differences. Participants reduced their total calorie (kcal) (p = 0.039), protein (g/kg) (p = 0.009), carbohydrate (g/kg) (p = 0.023), and fat (g) (p = 0.036) intake over time. Creatine supplementation increases sleep duration on resistance training days in naturally menstruating females.